Isolation of chemical constituents from roots of morinda citrifolia l. using non-polar solvent / Siti Hasnaa Hayati Ahmad Tajudin - Ahmad Tajudin, Siti Hasnaa Hayati (Faculty Of Applied Sciences, 2019)
Experiment was conducted on root bark of Morinda citrifolia L. which belong to the family of Rubiaceae found throughout humid tropical region. This genus of species varies of medicinal value. Several objectives have been set up for this experiment which is to extract and isolate the chemical constituents from root bark of Morinda citrifolia L. and also to identify and elucidate the structure of the compound by using spectroscopic methods. Works on the isolation of compound from the hexane crude extract of root bark of Morinda citrifolia L. through a series of column chromatography have resulted on the isolation of nordamnacanthal and damnacanthal. All of these structures were established by spectroscopic analysis which includes 1D NMR, MS technique and comparing with previous work.